A high-precision prediction model of surface roughness in abrasive belt flexible grinding of aero-engine blade. (June 2021) - Wang, Tingting; Zou, Lai; Wan, Qinghong; Zhang, Xinghao; Li, Yingjie; Huang, Yun
Abstract: This study presents a numerical simulation method to precisely predict the machined surface topography of aero-engine blade while using abrasive belt grinding technique. Considering the effect of curvature change of blade on the elastic contact state, a complex simulation model of the contact deformation at grinding interface was established, and the numerical prediction model of nonlinear time-varying contact deformation in whole grinding process was obtained. Furthermore, this contact deformation law was superimposed on motion trajectory equation of abrasive particles to accurately obtain the space location of the grinding points. The formation of the belt surface morphology was obtained by blue-light scanning device and Johnson transform system. The machined surface roughness with different curvature changes were acquired through the generation algorithm of workpiece morphology under the conditions of different grain sizes and feed rates. The grinding experiments were conducted to obtain that the average error values between simulated and measured surface roughness of blade maintained at about 4%. In addition, the difference of surface roughness between blade convex and concave surface was detailly explained based on a mathematical model. This work can be used to provide a beneficial guidance for the high-precision prediction of surface roughness of grinding aero-engine blade.